D1 Receptor Mediated Dopaminergic Neurotransmission Facilitates Remote Memory of Contextual Fear Conditioning - Saito, Nae; Itakura, Makoto; Sasaoka, Toshikuni (Frontiers in Behavioral Neuroscience, 2022)
Dopaminergic neurotransmission via dopamine D1 receptors (D1Rs) is considered to play an important role not only in reward-based learning but also in aversive learning. The contextual and auditory cued fear conditioning tests involve the processing of classical fear conditioning and evaluates aversive learning memory. It is possible to evaluate aversive learning memory in two different types of neural transmission circuits. In addition, when evaluating the role of dopaminergic neurotransmission via D1R, to avoid the effects in D1R-mediated neural circuitry alterations during development, it is important to examine using mice who D1R expression in the mature stage is suppressed. Herein, we investigated the role of dopaminergic neurotransmission via D1Rs in aversive memory formation in contextual and auditory cued fear conditioning tests using D1R knockdown (KD) mice, in which the expression of D1Rs could be conditionally and reversibly controlled with doxycycline (Dox) treatment. For aversive memory, we examined memory formation using recent memory one day after conditioning, and remote memory two weeks after conditioning. Furthermore, immunostaining of the brain tissues of D1RKD mice was performed after aversive footshock stimulation to investigate the distribution of activated c-Fos, an immediate-early gene, in the hippocampus (CA1, CA3, dentate gyrus), striatum, amygdala, and prefrontal cortex during aversive memory formation. After aversive footshock stimulation, immunoblotting was performed using hippocampal, striatal, and amygdalar samples from D1RKD mice to investigate the increase in the amount of c-Fos and phosphorylated SNAP-25 at Ser187 residue. When D1R expression was suppressed using Dox, behavioral experiments revealed impaired contextual fear learning in remote aversion memory following footshock stimulation. Furthermore, expression analysis showed a slight increase in the post-stimulation amount of c-Fos in the hippocampus and striatum, and a significant increase in the amount of phosphorylated SNAP-25 in the hippocampus, striatum, and prefrontal cortex before and after stimulation. These findings indicate that deficiency in D1R-mediated dopaminergic neurotransmission is an important factor in impairing contextual fear memory formation for remote memory.